2008
DOI: 10.1007/s00330-008-1014-x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma presenting as a musculoskeletal soft tissue mass: MRI findings in 24 cases

Abstract: The purpose was to describe the MRI morphological features and signal intensity (SI) characteristics of 24 histologically proven cases of musculoskeletal soft tissue lymphoma presenting clinically as a suspected primary soft tissue sarcoma. This was a retrospective review of clinical notes and MRI studies of 24 patients with a histologically confirmed diagnosis of lymphoma. All patients presented to a specialist orthopaedic oncology unit with a suspected primary soft tissue sarcoma. Features assessed included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
64
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 22 publications
3
64
1
1
Order By: Relevance
“…Suresh et al found that muscle lymphoma had a propensity to involve multiple muscle compartments, distinguishing it from most soft tissue sarcomas. Extension of muscle lymphoma into adjacent subcutaneous tissues was another interesting feature they reported and was seen in our first case presented [15]. Lymphoma can sometimes present with a focal muscle mass as opposed to an infiltrative ill-defined abnormality, but this is less common [16].…”
Section: Discussionmentioning
confidence: 85%
“…Suresh et al found that muscle lymphoma had a propensity to involve multiple muscle compartments, distinguishing it from most soft tissue sarcomas. Extension of muscle lymphoma into adjacent subcutaneous tissues was another interesting feature they reported and was seen in our first case presented [15]. Lymphoma can sometimes present with a focal muscle mass as opposed to an infiltrative ill-defined abnormality, but this is less common [16].…”
Section: Discussionmentioning
confidence: 85%
“…The role of imaging studies in the diagnosis and treatment of muscle lymphomas has been discussed in various reports [6-8]. MRI is currently the most preferred method for the characterization of soft-tissue tumor.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Intramuscular lymphomas can present as solid muscle lesions or as diffuse muscle enlargement. [15][16][17][18] The present study showed that in most cases (71.6%), IFs were not diagnosed at the time of CT investigations. Therefore, it is important to check the skeletal musculature in radiological investigations.…”
Section: Discussionmentioning
confidence: 48%